PENERAPAN PEMBELAJARAN PROBLEM POSING TIPE POST SOLUTION POSING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK - Delisten, Eci Sannick; muchlis, effie efrida; M.Pd, Drs. Rusdi (JP2MS, 2020)
This study aims to find out how to improve the activities and learning outcomes of students by applying the problem posing learning model type post solution posing. This type of research is Class Action Research (CAR). The subject of this study were 32 students of class VII I of SMP Negeri 8 Kota Bengkulu in the even semester of the academic year 2018/2019. The instruments used were activity observation sheets, exercises for each meeting and tests of student learning outcomes. Learning activities of students can be improved by using the LKPD problem posing learning model type post solution posing, Group Learning, and Working Together. Increased learning activities of students in cycle I to cycle III in a row: 27 (criteria are quite active); 29.12 (active criteria); 32.8 (active criteria). While the learning outcomes of students can be improved by using the LKPD problem posing learning model type post solution posing, practice questions and also make new questions. Increased learning outcomes of students from the first cycle to the third cycle, namely 50.78; 73.92 and 87.16 with the percentage of classical learning completeness from cycle I to cycle III which is 28.12%, 65.62% and 84.37%.